Esthetic outcome after nasal reconstruction with paramedian forehead flap and bilobed flap. Issue 4 (April 2021) - Peters, Florian; Mücke, Matthias; Möhlhenrich, Stephan Christian; Bock, Anna; Stromps, Jan-Philipp; Kniha, Kristian; Hölzle, Frank; Modabber, Ali
Summary: The incidence of skin cancer, which often affects the facial skin, has risen worldwide. After resecting such facial lesions, plastic reconstruction is necessary in most cases. The paramedian forehead flap (PFF) and the bilobed flap (BF) are commonly used for nasal reconstruction, but whether patients and physicians are satisfied with the esthetics is undetermined? In this study, scar questionnaires (Manchester Scar Scale, Vancouver Scar Scale, and Patient and Observer Scar Assessment Scale) and optical three-dimensional (3D) imaging were used for subjective and objective evaluation of esthetical outcomes after plastic reconstruction of the nose in 30 patients. The distances between landmarks and changes in volume between the treated and both the mirrored, healthy side of the face as well as an untreated, matched control group were measured using the optical (3D) scans. The questionnaires ascertained whether the patient was content with the esthetical outcome of both flaps. In the opinion of the observer, the esthetical outcome of both flaps was sufficient; only a few of the measured distances differed significantly between the patients and the control group. However, the measured volume differences of the donor site of the flap differed significantly between the PFF group and the control group ( p  = 0.0078). The BF was used for smaller defects, while the PFF was used for major defects. Besides a greater donor-side morbidity for the PFF, both flaps led to esthetically sufficient results and could be used for the reconstruction of the nose depending on the defect size and localization.